The morphometric analysis of Al-Rmayleh Basin by using Geographic Information System - Eyed, Safea; ALwesh, Yara (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to use Geographic information system techniques in morphometric analyzing for Jableh basin, by building geodata base for morphometric characteristics of the basin using the digital elevation model for analyzing, extracting river streams, and analyzing this characteristics to know Basin's morphological meaning. The study has showed that the basin's area is (72.22 k.m2), which it's morphometric characteristics vary from each other, Because of the climate changing, geology and surface of the basin. The number of it's streams was (83 streams), and it had close same stream value, that leads to give it tree distribution shape, with (1.18 stream/k.m2) density.